PEMANFAATAN LAHAN DI KECAMATAN RATAHAN, KECAMATAN RATAHAN TIMUR DAN KECAMATAN PASAN KABUPATEN MINAHASA TENGGARA BERDASARKAN ZONA AGROEKOLOGI DENGAN MENGGUNAKAN SISTEM INFORMASI GEOGRAFIS - Astri Vandalia Elisabeth Naray; Johan Alexander Rombang; Jaelani ., Husain (AGRI-SOSIOEKONOMI, 2019)
This study aims to determine the direction of land use in Ratahan Subdistrict, Ratahan Timur and Pasan, Southeast Minahasa Regency, based on the Agroecology Zone using the application of Geographic Information Systems (GIS). The type of research used in this study is quantitative research with a method of data and spatial interpretation. The types of data used in the study are primary data and secondary data. The data generated is arranged in the form of information and spatial. The study was conducted in 3 (three) subdistricts namely Ratahan Subdistrict, Ratahan Timur Subdistrict and Pasan Subdistrict, Southeast Minahasa Regency, North Sulawesi Province, which were included in 1 (one) sub-district, Ratahan Sub-district. While the implementation time in April to June 2018. Analysis of the data used in this study where the resulting data is arranged in the form of data and spatial information, then compiling and analyzing data using the Quantum ArcGIS version 10.2 program application. Besides that, biophysical data analysis and agricultural potential data will be carried out. The results of the study based on the concept of land use in Ratahan Subdistrict, East Ratahan and Pasan results of agroecological zone maps using GIS obtained 32 zones from the results of analysis of soil type and slope data and climate type. The results of the analysis of the allocation in accordance with the conditions of land use (land cover) as well as the output of the map of Southeast Minahasa Regency RTRW space map in 2013, the agroecological zone can be divided into two main uses, namely protected zone and cultivation zone. In protected areas recommended in protected forests, water catchment areas, river borders and lake bordersaround the springs. Whereas in the cultivation area it is recommended to use land for agroforesty, rice fields, settlements, mixed farming, conservation settlements, plantations and production forest.*eprm*